Anxiolytic activities of Matcha tea powder, extracts, and fractions in mice: Contribution of dopamine D1 receptor- and serotonin 5-HT1A receptor-mediated mechanisms. (August 2019) - Kurauchi, Yuki; Devkota, Hari Prasad; Hori, Kengo; Nishihara, Yuiko; Hisatsune, Akinori; Seki, Takahiro; Katsuki, Hiroshi
Graphical abstract: Highlights: Matcha tea powder, extract, and fractions were analyzed for anxiolytic activity in mice. Matcha tea powder and ethanol extract (CSE) showed anxiolytic activity. Ethyl acetate fraction of CSE was found to be most active fraction. Match exerted anxiolytic effects through dopamine D1 and serotonin 5-HT1A receptors. Abstract: Matcha is thought to be beneficial for brain functions; however, only a few scientific studies have shown the effects of Matcha tea powder on psychiatric behavior. Here, we evaluated the anxiolytic activity of Matcha tea powder, and its hot water extract (CSW) and ethanol extract (CSE) in mice, using the elevated plus maze test. Oral administration of Matcha tea powder and CSE exerted anxiolytic effects. CSE was further fractionated into hexane soluble (CSEH), ethyl acetate soluble (CSEE) and water soluble (CSEW) fractions. Among the fractions, CSEE and CSEH exerted anxiolytic effects. Moreover, SCH23390, a dopamine D1 receptor blocker, and WAY100135, an antagonist of the serotonin (5-hydroxytryptamine: 5-HT) 1A receptor, prevented Matcha tea powder and CSEE from exerting their anxiolytic effects. These results suggest that Matcha tea powder exerts anxiolytic effect through the activation of the dopaminergic and serotonergic systems.